Perancangan Tata Letak Gudang Penyimpanan Material pada Perusahaan Air Minum dengan Menggunakan Metode Class Based Storage - Guntara, Prasatya; Vikaliana, Resista; Kurnia, Gita (Industrika : Jurnal Ilmiah Teknik Industri, 2024)
PDAM Tirta Musi Palembang is a regional company engaged in the supply of clean water, especially in the Palembang area. The company still has not implemented the warehousing method properly. This is indicated by the presence of material with the highest frequency of picking placed far from the entrance and exit of the warehouse, the occurrence of long queues when picking up material for a unit in the warehouse, the aisle is used as the placement of goods, the labeling of materials is uneven, and placing goods in the area empty without regard to entry and exit. For this reason, it is necessary to improve the layout of the warehouse using the ABC Class-Based Storage method. The use of this method is based on the ease of managing the movement of goods in/out based on the frequency of movement of goods. Based on the results of data processing carried out, the grouping of materials using ABC analysis was obtained, namely Class A (HDPE Pipe, Sealtape, Elbow PE, Ferulle, Knee GS, and PVC Glue), Class B (Foucet Elbow and Knee PVC) and Class C (PVC Pipe, Clam Saddle, Box Meter, GS Pipe, and PVC Headlight). The Material Handling costs incurred in the proposed layout amounted to IDR 45,910687 (61.64% savings) which reduced the total distance by 66.30%. Keywords: ABC Analysis, Class-Based Storage, Material Handling Costs, Warehouse Layout